An investigation of child maltreatment and epigenetic mechanisms of mental and physical health risk - Cicchetti, Dante (Dev Psychopathol, 2016)
In the present investigation, differential methylation analyses of the whole genome were conducted among a sample of 548 school-aged low-income children (47.8% female, 67.7% Black, M age=9.40 years), 54.4% of whom had a history of child maltreatment. In the context of a summer research camp, DNA samples via saliva were obtained. Using GenomeStudio, Methylation Module and the Illumina Custom Model, differential methylation analyses revealed a pattern of greater methylation at low methylation sites (n=197 sites) and medium methylation sites (n=730 sites) and less methylation at high methylation sites (n=907 sites) among maltreated children. The mean difference in methylation between the maltreated and nonmaltreated children was 6.2%. The relative risk of maltreatment with known disease biomarkers was also investigated using GenoGo MetaCore Software. A large number of network objects previously associated with mental health, cancer, cardiovascular systems, and immune functioning were identified evidencing differential methylation among maltreated and nonmaltreated children. Site-specific analyses were also conducted for ALDH2, ANKK1, and NR3C1 and results highlight the importance of considering gender and the developmental timing of maltreatment. For ALDH2, results indicated that maltreated girls evidenced significantly lower methylation compared to nonmaltreated girls, and maltreated boys evidenced significantly higher methylation compared to nonmaltreated boys. Moreover, early onset-not recently maltreated boys evidenced significantly higher methylation at ALDH2 compared to nonmaltreated boys. Similarly, children with early onset-non recent maltreatment evidenced significantly higher methylation compared to nonmaltreated children at ANKK1. The site-specific results were not altered by controlling for genotypic variation of respective genes. The findings demonstrate increased risk for adverse physical and mental health outcomes associated with differences in methylation in maltreated children and indicate differences among maltreated children related to developmental timing of maltreatment and gender in genes involved in mental health functioning.